Audit Kualitas Perangkat Lunak: Verifikasi Fungsionalitas Sistem Presensi Berbasis Web Menggunakan Standar ISO/IEC 29119 - Nurul Khotimah; Dodi Wagiyanto; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
The reliability of employee attendance systems is a crucial element in human resource management to ensure payroll data integrity and discipline, yet the transition from manual methods to web-based digital platforms often faces data validity challenges, particularly regarding vulnerabilities to user time manipulation (client-side manipulation) and data redundancy. This study aims to audit the software quality of a web-based attendance application built using Native PHP and MySQL database, with a primary focus on verifying the stability of the system's logic in handling server-side time and validating the attendance workflow sequence. The testing methodology adopted adheres to the ISO/IEC 29119 international standard using a Black Box Testing approach, where a total of 25 test cases were comprehensively designed covering user interface modules, check-in and check-out logic, database integrity, and input security using Boundary Value Analysis and Stress Testing techniques. The results demonstrate that the system achieved a 100% success rate (Pass Rate) with a "Zero Bug" status, proving robust in preventing local device time manipulation and effectively rejecting attendance data duplication. It is concluded that this application meets technical feasibility standards, possesses high stability, and is ready for implementation to support small and medium-scale business operations.